2023
DOI: 10.1021/acsomega.3c02030
|View full text |Cite
|
Sign up to set email alerts
|

Nanoadjuvants: Promising Bioinspired and Biomimetic Approaches in Vaccine Innovation

Abstract: Adjuvants are the important part of vaccine manufacturing as they elicit the vaccination effect and enhance the durability of the immune response through controlled release. In light of this, nanoadjuvants have shown unique broad spectrum advantages. As nanoparticles (NPs) based vaccines are fast-acting and better in terms of safety and usability parameters as compared to traditional vaccines, they have attracted the attention of researchers. A vaccine nanocarrier is another interesting and promising area for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 183 publications
(296 reference statements)
0
3
0
Order By: Relevance
“…The environmental stability of MOFs also makes them suitable for use in vaccines that require transport to remote areas. Research by Desai et al (2024) [ 148 ] showed that MOFs could maintain their structural integrity and functional properties under varying temperatures and humidity levels. This characteristic could be pivotal in the global fight against cancer, allowing vaccines to reach populations in less accessible regions without compromising efficacy and highlighting their broad-spectrum benefits and potential for next-generation vaccine development.…”
Section: Applications Of Fn-mofs In Immunotherapymentioning
confidence: 99%
“…The environmental stability of MOFs also makes them suitable for use in vaccines that require transport to remote areas. Research by Desai et al (2024) [ 148 ] showed that MOFs could maintain their structural integrity and functional properties under varying temperatures and humidity levels. This characteristic could be pivotal in the global fight against cancer, allowing vaccines to reach populations in less accessible regions without compromising efficacy and highlighting their broad-spectrum benefits and potential for next-generation vaccine development.…”
Section: Applications Of Fn-mofs In Immunotherapymentioning
confidence: 99%
“…1,2 Traditional drug delivery or systemic administration of a drug could have flaws such as nonspecific targeting, low efficacy, and inadvertent and obvious sideeffects. 3,4 The emerging field of smart drug delivery aims to design and develop delivery systems to address these flaws to target specific cells, tissues, and organs better and minimize the off-target side-effects. 5,6 The development of smart drug delivery systems has opened up new vistas for targeted drug delivery against numerous diseases including cancer, cardiovascular diseases, neurological disorders, and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery is a critical aspect of modern medicine that ensures effective and safe administration of therapeutic agents to the target site in the body 1,2 . Traditional drug delivery or systemic administration of a drug could have flaws such as nonspecific targeting, low efficacy, and inadvertent and obvious side‐effects 3,4 . The emerging field of smart drug delivery aims to design and develop delivery systems to address these flaws to target specific cells, tissues, and organs better and minimize the off‐target side‐effects 5,6 …”
Section: Introductionmentioning
confidence: 99%